The library : an illustrated history - Murray, Stuart A. P (New York, NY : Skyhorse Pub. ; Chicago : ALA Editions, 2009)
The first libraries appeared five thousand years ago in Southwest Asia's 'Fertile Crescent'... the birthplace of writing, some time before 3000 BCE," writes Stuart A.P. Murray, introducing his fascinating exploration into the history of the library. With the dawning of advanced civilization, the written word flourished and the need for libraries became paramount in many societies. Throughout the history of the world, libraries have been constructed, burned, discovered, raided, and cherished - while the treasures they housed evolved from early stone tablets, to beautifully illumined vellum, and to the mass-produced, bound paper books and the digital formats of our present day. The Library opens doors to the libraries of ancient Greece, early China, Renaissance England, and modern day America. This volume speaks to the book lover in all of us while offering a panoramic view of the history of libraries across the centuries. Incorporating beautiful illustrations, insightful quotations, and descriptions of many marvelous libraries - their books, patrons, and keepers - The Library is certain to provide a wealth of knowledge and enjoyment. Published with the cooperation of the American Library Association and with an introduction by Donald G. Davis, Jr. and a foreword by bestselling author Nicolas A. Basbanes, Stuart A.P. Murray's The Library takes the reader on a compelling and informative journey through the dynamic history of our beloved libraries."
The ancient libraries -- European libraries of the Middle Ages -- Asia and Islam -- Europe's high Middle Ages -- Renaissance to Reformation -- People of the book -- War and a golden age -- The library in colonial North America -- The library in the young United States -- Libraries across America -- Organiztion knowledge -- Libraries, librarians, and media centers
Includes bibliographical references and index
Keywords: Libraries -- History; Libraries -- Pictorial works